Expression of an Engineered Heterologous Antimicrobial Peptide in Potato Alters Plant Development and Mitigates Normal Abiotic and Biotic Responses - Goyal, Ravinder K.; Hancock, Robert E. W.; Mattoo, Autar K.; Misra, Santosh (PLOS ONE, 2013)
Antimicrobial cationic peptides (AMPs) are ubiquitous small proteins used by living cells to defend against a wide spectrum of pathogens. Their amphipathic property helps their interaction with negatively charged cellular membrane of the pathogen causing cell lysis and death. AMPs also modulate signaling pathway(s) and cellular processes in animal models; however, little is known of cellular processes other than the pathogen-lysis phenomenon modulated by AMPs in plants. An engineered heterologous AMP, msrA3, expressed in potato was previously shown to cause resistance of the transgenic plants against selected fungal and bacterial pathogens. These lines together with the wild type were studied for growth habits, and for inducible defense responses during challenge with biotic (necrotroph Fusarium solani) and abiotic stressors (dark-induced senescence, wounding and temperature stress). msrA3-expression not only conferred protection against F. solani but also delayed development of floral buds and prolonged vegetative phase. Analysis of select gene transcript profiles showed that the transgenic potato plants were suppressed in the hypersensitive (HR) and reactive oxygen species (ROS) responses to both biotic and abiotic stressors. Also, the transgenic leaves accumulated lesser amounts of the defense hormone jasmonic acid upon wounding with only a slight change in salicylic acid as compared to the wild type. Thus, normal host defense responses to the pathogen and abiotic stressors were mitigated by msrA3 expression suggesting MSRA3 regulates a common step(s) of these response pathways. The stemming of the pathogen growth and mitigating stress response pathways likely contributes to resource reallocation for higher tuber yield.